PENGARUH INPUT TERHADAP NILAI TAMBAH INDUSTRI PENGOLAHAN TEMBAKAU DI INDONESIA - Juliana, Ria; Kadir, Hainim; Setiawan, Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this researched is to identify and analyze the influence of raw materials cost, fuel cost and capital cost to value-added of tobacco processing industry in Indonesia. This research was used secondary data from the years 2000-2013, published by the Badan Pusat Statistik Indonesia. The analytical method used multiple linear regression analysis, the beta coefficient test and elasticity test with SPSS 21. The results of this research showed simultaneous raw materials cost, fuel cost and capital cost affect the value-added of tobacco processing industry in Indonesia. Partially fuel cost has no significant effect on the value-added of tobacco processing industry, while raw materials cost and capital cost significantly influence the value-added processing of the tobacco industry.The capital cost has a negative value. Raw materials cost have a dominant influence on value-added of tobacco processing industry in Indonesia.Keywords: Cost, Capital, Raw Materials, Value Added and Tobacco